The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.11.16.20232561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locus coeruleus integrity is related to tau burden and memory loss in autosomal-dominant Alzheimer’s disease

Abstract: Abnormally phosphorylated tau, an indicator of Alzheimer’s disease, begins to accumulate in the first decades of life in the locus coeruleus (LC), the primary source of cortical norepinephrine. Ensuing dysfunction in noradrenergic neuromodulation is hypothesized to contribute to Alzheimer’s progression. However, research into the role of the LC has been impeded by a lack of effective ways of assessing it in vivo. Advances in high-resolution brainstem magnetic resonance imaging (MRI) hold potential to investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 120 publications
2
20
0
Order By: Relevance
“…The new "omni-comprehensive" LC mask included the six LC MNI atlases previously published: 1) Keren [84] without encroaching the Median Raphe (MR) and the Dorsal Raphe (DR) defined by Beliveau et al (2015) [85] and the cerebellar white matter. Additionally, the new created LC "omni-comprehensive" mask included the LC meta-mask developed by Dahl et al (2021) [57], but with a larger and symmetrical rostro-caudal extent as to avoid induced lateralization biases in the analyses. Indeed, as pointed out by Betts et al [83], the LC asymmetries reported in certain MRI studies could be caused by MRI biases of how radiofrequencies are transmitted and received in the scanner.…”
Section: Region Of Interest (Roi) Masksmentioning
confidence: 99%
“…The new "omni-comprehensive" LC mask included the six LC MNI atlases previously published: 1) Keren [84] without encroaching the Median Raphe (MR) and the Dorsal Raphe (DR) defined by Beliveau et al (2015) [85] and the cerebellar white matter. Additionally, the new created LC "omni-comprehensive" mask included the LC meta-mask developed by Dahl et al (2021) [57], but with a larger and symmetrical rostro-caudal extent as to avoid induced lateralization biases in the analyses. Indeed, as pointed out by Betts et al [83], the LC asymmetries reported in certain MRI studies could be caused by MRI biases of how radiofrequencies are transmitted and received in the scanner.…”
Section: Region Of Interest (Roi) Masksmentioning
confidence: 99%
“…The new "omni-comprehensive" LC mask included the six LC MNI atlases previously published: 1) Keren [85] and the cerebellar white matter. Additionally, the new created LC "omni-comprehensive" mask included the LC meta-mask developed by Dahl et al (2021) [57], but with a larger and symmetrical rostro-caudal extent as to avoid induced lateralization biases in the analyses. Indeed, as pointed out by Betts et al [83], the LC asymmetries reported in certain MRI studies could be caused by MRI biases of how radiofrequencies are transmitted and received in the scanner.…”
Section: Region Of Interest (Roi) Masksmentioning
confidence: 99%
“…To this end, we adopted a neuroimaging voxel-based morphometry (VBM) approach utilizing 3T T1-weighted structural MRI scans from 686 subjects [n=395 (HC), n=156 (MCI), and 135 (AD)] provided by Alzheimer's Disease Neuroimaging Initiative -ADNI (ADNI2 and ADNI3 phases) [49,50]. Structural volumetric analyses on 3T T1-weighted MRIs with this methodology have been already carried out by several studies showing accurate reliability investigating the integrity of the Brainstem [51,52,53,54], the LC also in the ADNI [55,56,57,58] and the other neuromodulators' seeds such as the Raphe Nuclei [59,60,61,62], the Ventral Tegmental Area (VTA) [63,64,65,66] and the Nucleus Basalis of Meynert (NBM) [67,68,69,70,71,72,73,74]. The main objectives of this study were threefold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we adopted a neuroimaging voxel-based morphometry (VBM) approach utilizing 3T T1-weighted structural MRI scans from 686 subjects [n=395 (HC), n=156 (MCI), and 135 (AD)] provided by Alzheimer Disease Neuroimaging Initiative -ADNI (ADNI2 and ADNI3 phases) [49,50]. Structural volumetric analyses on 3T T1-weighted MRIs with this methodology have been already carried out by several studies showing accurate reliability investigating the Brainstem [51,52,53,54], the LC also in the ADNI [55,56,57,58] and the other neuromodulators' seeds such as the Raphe Nuclei [59,60,61,62], the Ventral Tegmental Area [63,64,65,66] and the Nucleus Basalis of Meynert [67,68,69,70,71,72,73,74]. The main objectives of this study were threefold.…”
Section: Introductionmentioning
confidence: 99%